Mitochondrial Bioenergetic Metabolism Is Associated with Total Body Composition and Influenced by Normal Weight Obesity (P21-039-19). (13th June 2019) - Bellissimo, Moriah; Fleischer, Candace; Tran, Phong; Hao, Li; Reiter, David; Smith, Matthew; Boebinger, Scott; Wells, Greg; Jones, Dean; Ziegler, Thomas; Alvarez, Jessica
Abstract: Objectives: Obesity, body composition, and mitochondrial dysfunction play important roles in the development of metabolic diseases, but it is unknown if increased visceral fat (VF) specifically alters mitochondrial bioenergetic capacity. We determined whether in vivo and ex vivo bioenergetic indexes are associated with total body composition, visceral fat (VF), and body composition subtypes. Methods: This pilot study included 34 healthy adults (56% female, median age 27.9 y). Body composition and fat distribution were assessed by dual energy x-ray absorptiometry. Subjects were categorized as lean (BMI < 25 kg/m 2, n = 14), normal weight obese (NWO, BMI < 25 kg/m 2 and >30% body fat in women or >23% body fat in men, n = 8), or overweight/obese (O/O, BMI > 25 kg/m 2, n = 12). Ex vivo mitochondrial function was assessed using a Seahorse extracellular flux analyzer in peripheral blood mononuclear cells (PBMC) and isolated monocytes. In a subset ( n = 21), maximum in vivo ATP synthesis was assessed in the quadriceps using 31P-Magnetic resonance spectroscopy based on the phosphocreatine recovery time constant (τPCr) following a standardized leg exercise. Statistical analyses included Spearman correlations and Kruskal-Wallis tests. Results: In monocytes, but not PBMCs, % spare respiratory capacity was inversely associated with % body fat ( r = −0.42, P = 0.02) and positively associated with lean body mass ( r = 0.36, P = 0.04) but was not significantly associated with VF. Skeletal muscle τPCr was positively associated with % body fat ( r = 0.58, P < 0.01) and total body fat ( r = 0.53, P = 0.02) but not VF. Subjects with NWO had the highest τPCr ( P = 0.01) and lowest % spare respiratory capacity ( P = 0.09 and 0.03 in monocytes and PBMCs, respectively) compared to lean or O/O subjects. Conclusions: Total body fat, but not VF, was associated with impaired mitochondrial function as shown by increased post-exercise recovery time in skeletal muscle and decreased response to energy demands in circulating cells. Adults with NWO had worse bioenergetic capacity than O/O or lean adults. These data provide insight on the relationships between human body composition and mitochondrial energy metabolism, which plays a role in metabolic disease progression. Funding Sources: National Institutes of Health, Georgia Clinical and Translational Science Alliance.